Exploring User Nature Experience in Urban Green Spaces through Biophilic Design - Koray VELIBEYOĞLU (Journal of Urban and Regional Analysis)
Increasing urbanisation limits human interaction with natural envi$ ronments, underscoring the critical importance of urban green spaces for daily nature engagement. Biophilic design, which focuses on enhancing human interactions with nature in the built environment, provides an opportunity to fosterthis engagement. This study investigates how the characteristics of urban green spaces impact the users' nature experiences within the experience$ based framework of biophilic design. Focusing on three neighbourhood parks in the Bostanlı neighbourhood of Karşıyaka district, Izmir (Türkiye), the research evaluates nature experiences at both environmental and individual levels. The environmental level analysis assessed the nature experience potential of each park, while a nature experience workshop gathered insights into individual nature experiences. The findings indicate that nature experiences in urban green spaces are influenced by a combination of individual and environmental factors, challenging the effectiveness of a uniform approach in the design of these spaces. The study also provides empirical evidence that specific park characteristics—such as quietness, vegetation, size, accessibility, and sense of place—influence the users' nature experiences. This research highlights the value of the experience based framework of biophilic design for understanding and enhancing user nature interactions and it underscores its importance in guiding future urban green space planning and design strategies.